Competition Law in the Digital Era: Perspective on Startup Companies in Indonesia - Mustafa, Abraham Reyhand; Hardyansah, Rommy; Putra, Arif Rachman; Wibowo, Agung Satryo; Negara, Dharma Setiawan (Metromedia, 2025)
Business competition in the digital era presents new challenges for startups in Indonesia, such as the dominance of large platforms, algorithmic discrimination, and the lack of digital infrastructure. Law Number 5 of 1999 as the legal basis for business competition has not fully accommodated technological developments such as algorithms, big data, and the digital ecosystem. This research analyzes the application of competition regulations to startups in the digital era, focusing on challenges such as market access inequality and the lack of legal education. Additionally, this research explores opportunities such as the use of disruptive technology and collaboration between startups and regulators. With a normative-empirical approach, this research examines the relevance of current regulations and provides strategic recommendations to create a fair and sustainable digital business ecosystem. The research results indicate that revising regulations to be responsive to the digital era is essential to support healthy competition and innovation in the startup sector.